Strategi Pengembangan Potensi Usaha Mikro, Kecil, dan Menengah Kerajinan Tangan Kiso “Jago Abadi” Di Desa Kemiri, Kabupaten Banyumas - Muflih Nurriza Pahlawi; Abu Dharin (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2021)
Small and Medium Enterprises (MSMEs) are an inseparable part of the national business world. The existence of MSMEs is something that is quite vital in improving the economy of the Indonesian people in various regions. This study aims to analyze the development strategy of the Kiso